Assessment of Shoulder Function after Internal Fixation of Humeral Diaphyseal Fractures in Young Adults: A Prospective Comparative Study. (1st November 2021) - Mahmoud, Hossam Fathi; Farhan, Ahmed Hatem; Fahmy, Fahmy Samir
Abstract : Background . Humeral shaft fractures are commonly encountered in casualties. There are different methods of operative internal fixation with no consensus on the best technique. The objective of this study was to assess shoulder function and rate of complications among two different options of fixation, intramedullary nailing, and minimal invasive plate osteosynthesis (MIPO) in young adults. Methods . Forty-two patients with humeral shaft fractures were included in the study and divided into two equal groups: group A treated with antegrade intramedullary locked nails (IMN) and group B with MIPO. Fracture union was evaluated with serial X-rays, and shoulder function was assessed in both groups using the scale of the American Shoulder and Elbow Surgeons (ASES), University of California at Los Angeles Shoulder Scale (UCLA), and visual analog score (VAS). The mean differences between groups were recorded and considered significant if the P value was ˂0.05. Results . The results were reported prospectively with no significant differences in mean age, sex, side of injury, type of fracture, mechanism of injury, and the follow-up period between the groups studied. Group A had shorter operative time and minimal blood loss than group B. Regarding shoulder function scores (ASES, UCLA, and VAS), the results in the MIPO group were better than the IMN group with shorter time of union and fewer complications. Conclusion . Despite a shorter operative time and lower blood loss during locked intramedullary nail fixation in the management of humeral shaft fractures, MIPO enables more superior shoulder function with better fracture healing and lower morbidities.